Epidemiology and risk factors of table-tennis-related injuries: findings from a scoping review of the literature - Biz, C.; Puce, L.; Slimani, M.; Salamh, P.; Dhahbi, W.; Bragazzi, N. L.; Ruggieri, P. (Medicina, 2022)
Background and Objectives: Table tennis represents one of the fastest ball games in the world and, as such, is characterized by unique physiological demands. Despite its popularity, there is a dearth of data related to table-tennis-related risk factors and injuries. Therefore, the present review was conducted to fill in this gap of knowledge.